Preparation method of alpha alumina nano powder with large specific surface area

By co-grinding an organic acid abrasive agent and alumina raw materials, the problem of difficult to prepare high specific surface area α alumina nanopowder in industrial production in the prior art is solved, and an efficient and simple preparation process is achieved. The obtained nanopowder has excellent particle size distribution and purity.

CN119898804APending Publication Date: 2025-04-29SHANGHAI MIMINA NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311395680.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, it is difficult to effectively prepare α alumina nanopowder with an average particle size less than 15 nanometers and a specific surface area greater than 100 m2/g in industrial production. The commonly used methods are inefficient, low yields, and complex processes.

Method used

The organic acid aid is used to co-grind with alumina raw materials, and grind it through a planetary ball mill, combined with ethanol centrifugal washing and diluted hydrogen peroxide nitric acid solution, remove the debris of the grinding medium and the residual organic acid, and finally dry in vacuum to obtain high-purity large specific surface area α alumina nanopowder.

Benefits of technology

It is realized that the α alumina nano powder with an average particle size of less than 15 nanometers and a specific surface area of ​​more than 100m2/g is simply and efficiently prepared, which reduces material consumption and energy consumption, improves the purity and dispersion of the powder, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898804A_ABST
    Figure CN119898804A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of large-specific-surface-area alpha aluminum oxide nanopowder, the nanopowder refers to powder with the average particle size smaller than 15 nanometers, the large specific surface area refers to that the BET surface area is larger than 100 m < 2 > / g, and the preparation method comprises the following steps: A) grinding a blend of an aluminum oxide raw material and an organic acid grinding aid by using a grinding medium, wherein the grinding aid is organic acid. A subsequent separation and purification step can also be included to prepare high-purity large-specific-surface-area alpha-alumina nanopowder. According to the method, raw materials are easy to obtain, the technological process is simple, the yield is close to 100%, and industrial production prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nano material preparation, and specifically relates to a method for preparing a large specific surface area α-alumina nano powder. Background Art

[0002] Alumina has become one of the most widely used basic materials due to its excellent performance and low price. As the most stable phase of alumina, α-alumina has the characteristics of corrosion resistance and high temperature resistance, high strength and hardness, wear resistance, good insulation, etc. It is widely used in defense, aerospace, electronics, chemical industry, medicine, nuclear industry and other fields, and is one of the important basic raw materials in many high-tech fields.

[0003] The excellent physical and chemical properties of α-alumina nanopowder due to its size effect have doubled its value. For example, its extremely fine size can be used in nano-polishing agents. Due to its large specific surface area and structural stability, it can be directly used as a carrier for automobile exhaust catalysts, or as a high-efficiency catalyst for ammonia preparation, etc. In addition, for the firing of α-alumina ceramics, as the α-alumina nanopowder is refined or the specific surface area increases, its sintering temperature gradually decreases and the density and fracture strength are higher. If the particle size of the sintered nanoparticles can be controlled at a smaller nano size, α-alumina ceramics may even show good plasticity. Therefore, the preparation of α-alumina nanopowders also provides a basis for solving the brittleness problem of alumina ceramics. In short, how to simply prepare α-alumina nanopowders with smaller particle size or high specific surface area is of great significance.

[0004] The current preparation methods of α-alumina nanopowders mainly include microemulsion method (Y. Pang and X. Bao. J. Mater. Chem., 12 (2002) 3699-3704), sol-gel method (J. Li, et al. Ceram. Int., 32 (2006) 587-591), precipitation method (J. Li and X. Sun. Acta mater., 48 (2000) 3103-3112) and spray pyrolysis method (RM Laine, et al. Nature Mater., 5 (2006) 710-712). However, these methods generally require calcination or pyrolysis at above 1000°C, which leads to an increase in particle size and serious agglomeration. Therefore, although people have tried various methods to prepare α-alumina powders with high specific surface area in the past few decades, it is difficult to succeed because the preparation of particle size less than 15 nanometers and specific surface area greater than 100m 2 / g of α-alumina powder is a recognized technical challenge in the industry, which is also acknowledged in the world's top academic journal "Science". For details, see AP Amrute, et al., Science, 366 (2019) 485-489.

[0005] In addition, all of the above methods have some defects and are difficult to apply to industrial production. For example, by first preparing diaspore and then high-pressure hydrothermal reaction, a material with a specific surface area greater than 150m 2 / g of α-alumina nanopowder. However, this method has too high requirements for preparation conditions and requires 35 days of reaction under high pressure, resulting in low industrial value (T.Tsuchidaand K.Kodaira, J.Mater.Sci., 25 (1990) 4423–4426). Amrute et al. used mechanochemical methods to directly convert boehmite into high-surface-area α-alumina nanopowder (APAmrute, et al.Science, 366 (2019) 485-489). However, this method has been questioned by many other scientists (see J.Li, et al.Science, (2020) 10.1126 / science.abb0142). Although Amrute et al. responded to these questions in an academic journal (see AP Amrute, et al. Science, (2020) 10.1126 / science.abb0948), the inventor of this patent believes that the biggest problem with this method is that the conversion efficiency of boehmite and the specific surface area of ​​the final product are affected by the water content of boehmite. Therefore, it is necessary to first prepare boehmite with a certain water content and ensure that the water content can be maintained within a certain range during its structural change process, which is difficult to achieve in actual industrial production.

[0006] Chinese patents CN106044809A and CN104495891A also report the preparation of ultrafine α-alumina powder with large specific surface area. However, the core technical features of these patented methods can be simply summarized as follows: the raw materials for preparing α-alumina are ball-milled in a high-energy ball mill to obtain a mixture of α-alumina powders of various sizes. The mixture is corroded by soaking in concentrated hydrochloric acid for a long time, and then subjected to multiple graded agglomeration separations to obtain some of the particles with a particle size of less than 15 nanometers and a specific surface area of ​​more than 100 m 2 / g of α-alumina powder. Although these patents only briefly mention multiple soakings in hydrochloric acid and do not explicitly mention the concept of graded coagulation separation, the real trick lies precisely in these multiple hydrochloric acid soaking processes. From the papers published by the inventors of these patents at the same time (L. Li, et al. Adv. Powder Technol., 29 (2018) 2194-2203 and S. Pu, et al. Sci. Rep., 5 (2015) 11575), it can be seen that the particle size distribution of their products after high-energy ball milling is still extremely wide. After 100 hours of ball milling and soaking in concentrated acid, only 40% of the particles are less than 100 nanometers in size. Therefore, it can be inferred that the proportion of particles less than 15 nanometers will be even smaller. Subsequent operations of graded coagulation separation of particles according to particle size must be carried out with hydrochloric acid multiple times to finally obtain that small proportion of particles with a size less than 15 nanometers and a specific surface area greater than 100m 2 / g of α-alumina powder. According to the patent, these particle size classification and coagulation and sedimentation operations need to be carried out multiple times using concentrated hydrochloric acid, which causes serious corrosion and pollution to the equipment. In addition, the particle size classification process takes more than 80 hours in total. Such a long post-treatment process and such a low yield of the target product obviously cannot meet the needs of industrial production.

[0007] Furthermore, the experiment of directly ball milling α-alumina powder for a long time in the above two patents is difficult to operate in actual experiments. Because the adhesion between alumina powders is very strong, agglomeration and bonding phenomena begin to appear after half an hour of grinding, and basically agglomerates at the bottom of the jar after about two hours of grinding. The inventor tried many times, but failed to adjust the ball mill speed or use different grinding balls. The only feasible method is to open the jar and turn it over every one or two hours. Because no grinding aid is added, it is difficult to reach the nanometer level in the microscopic powder particle size, and most of it is still micron-level powder. Therefore, the real principle of the methods of these two patents is: relying on ball milling to perform large plastic deformation on submicron-level alumina to produce many grain boundaries, and then soaking and corroding with acid for a long time many times. Corrosion mainly corrodes grain boundaries, because the atomic bonding force of grain boundaries is weak and there may be some holes. Long-term and multiple corrosion can disperse some small particles from large particles, thereby obtaining particles of different particle sizes, and then centrifugation is used to remove large submicron-level particles. The powder is separated by graded coagulation with hydrochloric acid. Therefore, these two patents not only have low efficiency but also extremely low yield, and are not suitable for industrial production.

[0008] In fact, before the publication of the above two patents, Russian researchers had done similar work (see GR Karagedov and NZ Lyakhov, Nanostruct. Mater., 11 (1999) 559-572). The difference is that they added a confidential "grinding catalyst", and then used an extremely high ball milling speed to complete the experiment within tens of minutes, and then soaked it in hydrochloric acid to obtain α-alumina nanopowder. The purpose of doing this may be because the powder is very easy to agglomerate, so it can only be completed in a very short time by adding a "grinding catalyst" and under intense ball milling. Ball milling reaches equilibrium within half an hour. If you want to extend the time, the powder cannot be further refined and will cause re-agglomeration (GR Karagedov and NZ Lyakhov, KONA Powder & Part. J., 21 (2003) 76-87). Therefore, the minimum average particle size of the powder they obtained is only 25nm, and the maximum specific surface area is less than 80m 2 / g.

[0009] Therefore, how can we prepare a material with an average particle size of less than 15 nanometers and a specific surface area of ​​more than 100m by an industrially feasible method? 2 / g of α-alumina powder has always been a huge technical challenge in this field.

[0010] The present invention aims to solve this problem. Summary of the invention

[0011] The first aspect of the present invention provides a method for preparing α-alumina nanopowder with a large specific surface area, wherein the nanopowder refers to a powder with an average particle size of less than 15 nanometers, and the large specific surface area refers to a BET surface area greater than 100 m 2 / g, the method comprises the following steps:

[0012] A) grinding a mixture of alumina raw material and an organic acid grinding aid with a grinding medium, wherein the grinding aid is an organic acid.

[0013] There is no restriction on the crystal form and initial particle size of the alumina raw material. For example, the alumina raw material can be selected from thermodynamically metastable transition phase alumina such as amorphous alumina, γ alumina, δ alumina, η alumina, θ alumina, λ alumina, κ alumina, ρ alumina, χ alumina, and α alumina or a mixture of at least two of them; its particle size can be millimeter-level, micrometer-level, submicrometer-level or nanometer-level. Since α alumina is the most thermodynamically stable crystal form among many alumina crystal forms, no matter what crystal form the starting alumina raw material has, it will eventually be converted into α-type after sufficient grinding time. Of course, no matter what the initial particle size is, the final particle size can reach nanometer level under continuous grinding.

[0014] Wherein said organic acid is selected from carboxylic acid, organic sulfonic acid, organic sulfinic acid or thiocarboxylic acid. There is no restriction on the type of specific organic acid, as long as it has an acidic group and an organic group. These organic acids can react with a large amount of hydroxyl groups on the surface of aluminum oxide, so that their acid radicals undergo strong chemical adsorption on the surface of aluminum oxide. The surface energy of aluminum oxide powder adsorbed with a large amount of organic acid radicals is low, which reduces the adhesion between powder particles, avoids its agglomeration and growth in the mechanochemical process, and keeps it in a high specific area state. Common organic acids such as capric acid, caprylic acid, caproic acid, lauric acid, myristic acid, citric acid, malic acid, salicylic acid, benzenesulfinic acid, etc. can be used.

[0015] There is no limitation on the mixing method of the organic acid grinding aid and the alumina raw material. The two can be mixed in proportion in advance and then ground together, or the alumina can be ground first and then the organic acid can be added midway. The time point and amount of adding the organic acid can also be determined by technicians in this field through experiments.

[0016] The ratio of the organic acid grinding aid to the alumina raw material is 0.1-1 mmol / g. If the ratio is lower than 0.1 mmol / g, the organic acid grinding aid is too little to sufficiently modify the surface of the alumina powder. If the ratio is higher than 1 mmol / g, the organic acid grinding aid is greatly excessive, which does not affect the technical effect but is not necessary economically.

[0017] Wherein, the grinding can be selected from conventional grinding techniques in the art, for example, planetary ball milling, vibrating ball milling, stirring ball milling or bead milling. There is no restriction on the grinding medium, and any commonly used grinding medium can be used, because the grinding medium usually has the characteristics of high hardness and wear resistance, such as corundum balls, stainless steel balls, tungsten steel balls, zirconium dioxide balls, tungsten carbide balls, wherein tungsten carbide balls with high hardness and low wear are preferably used. There are no special requirements for grinding temperature, grinding time, grinding intensity, etc., and those skilled in the art can determine the appropriate grinding temperature, grinding time and grinding intensity required for grinding to the desired particle size by conventional experimental means. Preferably, the grinding medium is a stainless steel ball, a tungsten steel ball, a corundum ball, a zirconium dioxide ball or a tungsten carbide ball, the ball-to-material mass ratio is 10:1 to 60:1, the ball mill speed is 200-500rpm, the grinding temperature is room temperature to 200°C, and the grinding time is 10 to 70 hours. Grinding can be carried out in air without vacuum or inert gas protection.

[0018] From the perspective of preparation alone, the present invention only requires the above-mentioned step A to prepare the target product, but the obtained target product will inevitably contain grinding medium debris and residual organic acid grinding aids. Therefore, if a high-purity target product is to be prepared, in a preferred embodiment of the present invention, after the grinding step, the following separation and purification steps shown in steps B, C, and D are also required.

[0019] In step B, the organic acid grinding aid contained in the ground powder is preliminarily removed by solvent washing; this step is an optional step, and when the amount of the oxidant in the subsequent step C is sufficient, this step B can be omitted.

[0020] In step C, the ground powder is added to a mixed solution of an inorganic acid and an oxidant to remove the grinding medium debris and residual organic acid grinding aids. The inorganic acid is used to completely dissolve the debris of grinding media such as stainless steel balls, tungsten steel balls, corundum balls, zirconium dioxide balls, etc. The inorganic acid can be nitric acid, sulfuric acid, hydrochloric acid, preferably dilute nitric acid; the oxidant is used to completely remove the residual organic acid grinding aids; the oxidant can be hydrogen peroxide, persulfate, perchloric acid or sodium hypochlorite, preferably hydrogen peroxide, because its decomposition product is water and no impurities will remain. For the grinding medium debris of tungsten carbide balls, it is mainly removed by oxidizing them into soluble tungstic acid under the condition of enhanced oxidizing property of inorganic acid with hydrogen peroxide.

[0021] In step D, the powder after removing the grinding media and organic acid grinding aid is washed with an inert solvent and then vacuum dried to obtain high-purity α-alumina nanopowder with a large specific surface area. The vacuum drying conditions and time can be specifically determined by technicians without difficulty.

[0022] The above technical solutions can be freely combined under the premise of no contradiction.

[0023] The present invention has the following beneficial effects:

[0024] (1) The present invention first discovered that the use of organic acid grinding aids and alumina raw materials for co-grinding can obtain alumina with an average particle size of less than 15 nanometers and a specific surface area of ​​more than 100 m in a simple, efficient and industrially feasible manner. 2 / g of α-alumina powder.

[0025] (2) The present invention has no restrictions on the initial particle size and crystal form of the alumina raw material. Regardless of the crystal form and the initial particle size, the method of the present invention can ultimately obtain an alumina raw material with an average particle size of less than 15 nanometers and a specific surface area of ​​more than 100 m 2 / g of α-alumina powder.

[0026] (3) The preparation method of the present invention does not require cumbersome particle size classification and agglomeration separation after grinding, and almost 100% of the initial alumina raw material is converted into a final average particle size of less than 15 nanometers and a specific surface area of ​​more than 100 m 2 / g of α-alumina powder, so the material consumption and energy consumption are much lower than the existing technical methods.

[0027] (4) The alumina raw material in the preparation method of the present invention is widely applicable, cheap and easy to obtain, the preparation process is simple and efficient, the reaction is mild, and the preparation process parameters are controllable. The α-alumina nanopowder obtained by the present invention has a small particle size and good dispersibility, and is high in purity, and is suitable for various high-precision applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is the X-ray diffraction (XRD) spectrum of the α-alumina nanopowder in Example 1 of the present invention;

[0029] Figure 2 This is a transmission electron microscope image of the α-alumina nanopowder in Example 1 of the present invention;

[0030] Figure 3 is a nitrogen adsorption-desorption curve of the BET test of the α-alumina nanopowder in Example 1 of the present invention;

[0031] Figure 4 is the X-ray diffraction (XRD) spectrum of the α-alumina nanopowder in Example 2 of the present invention;

[0032] Figure 5 The transmission electron microscope and electron diffraction images of the α-alumina nanopowder in Example 2 of the present invention are shown;

[0033] Figure 6 is a nitrogen adsorption-desorption curve of the BET test of the α-alumina nanopowder in Example 2 of the present invention;

[0034] Figure 7 is the X-ray diffraction (XRD) spectrum of the α-alumina nanopowder in Example 3 of the present invention;

[0035] Figure 8 The transmission electron microscope and electron diffraction images of the α-alumina nanopowder in Example 3 of the present invention are shown;

[0036] Fig. 9 is a nitrogen adsorption-desorption curve of the BET test of the α-alumina nanopowder in Example 3 of the present invention;

[0037] Fig.10 is the X-ray diffraction (XRD) spectrum of the α-alumina nanopowder in Example 4 of the present invention;

[0038] Fig.11 The transmission electron microscope and electron diffraction images of the α-alumina nanopowder in Example 4 of the present invention are shown;

[0039] Fig.12 This is the nitrogen adsorption-desorption curve of the BET test of the α-alumina nanopowder in Example 4 of the present invention.

[0040] Fig.13is the X-ray diffraction (XRD) spectrum of the α-alumina nanopowder in Example 5 of the present invention;

[0041] Fig.14 The transmission electron microscope and electron diffraction images of the α-alumina nanopowder in Example 5 of the present invention are shown;

[0042] Fig.15 is a nitrogen adsorption-desorption curve of the BET test of the α-alumina nanopowder in Example 5 of the present invention;

[0043] Fig.16 is the X-ray diffraction (XRD) spectrum of the α-alumina nanopowder in Example 6 of the present invention;

[0044] Fig.17 The transmission electron microscope and electron diffraction images of the α-alumina nanopowder in Example 6 of the present invention are shown;

[0045] Fig.18 is a nitrogen adsorption-desorption curve of the BET test of the α-alumina nanopowder in Example 6 of the present invention;

[0046] Fig.19 is the X-ray diffraction (XRD) spectrum of the α-alumina nanopowder in Example 7 of the present invention;

[0047] Fig. 20 The transmission electron microscope and electron diffraction images of the α-alumina nanopowder in Example 7 of the present invention are shown;

[0048] Fig.21 The nitrogen adsorption-desorption curve of the BET test of the α-alumina nanopowder in Example 7 of the present invention is DETAILED DESCRIPTION

[0049] The content of the present invention is further illustrated below through specific implementation modes, but it is not intended to limit the present invention.

[0050] Example 1

[0051] This embodiment 1 uses a specific surface area of ​​about 5m 2 / g of submicron α-alumina powder was used as raw material, and decanoic acid CH3(CH2)8COOH was added as a grinding aid, and ground into a powder with a specific surface area of ​​102m 2 / g of α-alumina nanopowder, the specific steps are:

[0052] a. Place about 750 g of tungsten carbide grinding balls (i.e., the grinding medium is tungsten carbide) with a ball diameter of 1 cm in a 250 ml tungsten carbide ball mill;

[0053] b. Alumina and decanoic acid were added in an amount of 0.35 mmol decanoic acid per gram of alumina so that the total weight of the material was about 25 g;

[0054] c. The ball mill was placed on a planetary ball mill (produced by Nanjing University, model QM-3SP2, with a rotation speed to revolution speed ratio of -2:1) and the revolution speed was set to 290 revolutions per minute. The ball mill was paused for 10 minutes after every 30 minutes of milling. After a total milling time of 60 hours, the ball mill was opened to obtain a gray powder.

[0055] d. Wash the powder once with ethanol by centrifugation to remove most of the decanoic acid; this step d generally takes a few minutes to complete;

[0056] e. Continue to add the powder to the quartz flask in the solution of hydrogen peroxide and dilute nitric acid. The amount of solution used is: according to the mass of the powder before washing with ethanol, 30g of 2g of 65wt.% nitric acid and 28g of hydrogen peroxide containing 30wt.% hydrogen peroxide are added per gram of powder. Then, the quartz flask is placed in a 120-degree oil bath and refluxed for 15 minutes to remove tungsten carbide debris and residual organic acid; the whole process of step e takes about 30-40 minutes;

[0057] f. After the powder is separated from the solid and liquid and cooled, it is centrifugally washed twice with deionized water and then once with ethanol. This washing step takes no more than 40 minutes. The powder is then placed in a vacuum drying oven at 70 degrees for 12 hours to obtain the target powder.

[0058] Figure 1 This is the XRD spectrum of the α-alumina powder obtained in Example 1, which shows a pure α-alumina phase. The grain size is estimated by using the Scherrer formula on the XRD spectrum, and the obtained grain size is about 11 nm. Figure 2 This is a transmission electron microscope image of the α-alumina powder obtained in Example 1. From the electron microscope image statistics, it is found that the average particle size of the nanoparticles is about 14 nanometers, the particle size distribution is narrow, and the powder has good dispersibility. Figure 3 The nitrogen adsorption-desorption curve of the α-alumina powder obtained in Example 1 is in accordance with the H3 type published by the International Union of Pure and Applied Chemistry, indicating that the obtained powder is a soft agglomerated powder, which once again proves that the powder has good dispersibility. The specific surface area of ​​the α-alumina is calculated by the formula through the adsorption-desorption curve to be 102m 2 / g. The sample purity was measured by ICP-OES and was about 99wt.%.

[0059] Example 2

[0060] In this embodiment 2, the specific surface area used is about 5m 2 / g of submicron α-alumina powder as raw material, adding lauric acid CH3(CH2) 10 COOH is used as a grinding aid and ground into a powder with a specific surface area of ​​104m 2 / g of α-alumina nanopowder, the specific steps are:

[0061] a. Place about 750 g of tungsten carbide grinding balls (i.e., the grinding medium is tungsten carbide) with a ball diameter of 1 cm in a 250 ml tungsten carbide ball mill;

[0062] b. Alumina and lauric acid were added in an amount of 0.35mmol lauric acid per gram of alumina raw material so that the total weight of the material was about 25 grams;

[0063] c. The ball mill was placed on a planetary ball mill (produced by Nanjing University, model QM-3SP2, with a rotation speed to revolution speed ratio of -2:1) and the revolution speed was set to 290 revolutions per minute. The ball mill was paused for 10 minutes every 30 minutes of milling. After a total milling time of 50 hours, the ball mill was opened to obtain a gray powder.

[0064] d. Wash the powder once by centrifugation with ethanol to remove most of the lauric acid; this step d generally takes a few minutes to complete;

[0065] e. Continue to add the powder to the quartz flask in the solution of hydrogen peroxide and dilute nitric acid. The amount of solution used is: according to the mass of the powder before washing with ethanol, 30g of 2g of 65wt.% nitric acid and 28g of hydrogen peroxide containing 30wt.% hydrogen peroxide are added per gram of powder. Then, the quartz flask is placed in a 120-degree oil bath and refluxed for 15 minutes to remove tungsten carbide debris and residual organic acid; the whole process of step e takes about 30-40 minutes;

[0066] f. After the powder is separated from the solid and liquid and cooled, it is centrifugally washed twice with deionized water and then once with ethanol. This washing step takes no more than 40 minutes. The powder is then placed in a vacuum drying oven at 70 degrees for 12 hours to obtain the target powder.

[0067] Figure 4 This is the XRD spectrum of the α-alumina powder obtained in Example 2, which shows a pure α-alumina phase. The grain size is estimated by using the Scherrer formula on the XRD spectrum, and the obtained grain size is about 10 nm. Figure 5 This is a transmission electron microscope image of the α-alumina powder obtained in Example 2. The average particle size of the particles obtained from the transmission electron microscope image is about 13 nanometers, the particle size distribution is narrow, and the powder has good dispersibility. Figure 6 The nitrogen adsorption-desorption curve of the α-alumina powder obtained in Example 2 is a composite H3 type published by the International Union of Pure and Applied Chemistry, indicating that the obtained powder is a soft agglomerated powder, which once again proves that the powder has good dispersibility. The specific surface area of ​​α-alumina is calculated by the formula through the adsorption-desorption curve to be 104m 2 / g. The sample purity was measured by ICP-OES and was about 99wt.%.

[0068] Example 3

[0069] In this embodiment 2, a specific surface area of ​​170 m 2 / g of γ-alumina was prepared by adding hexanoic acid CH3(CH2)4COOH as a grinding aid to obtain a specific surface area of ​​137m 2 / g of α-alumina nanopowder, the specific steps are:

[0070] a. Place about 750 g of tungsten carbide grinding balls (i.e., the grinding medium is tungsten carbide) with a ball diameter of 1 cm in a 250 ml tungsten carbide ball mill;

[0071] b. Alumina and caproic acid were added in an amount of 0.3 mmol caproic acid per gram of alumina raw material so that the total weight of the material was about 25 grams;

[0072] c. The ball mill was placed on a planetary ball mill (produced by Nanjing University, model QM-3SP2, with a rotation speed to revolution speed ratio of -2:1) and the revolution speed was set to 290 revolutions per minute. The ball mill was paused for 10 minutes every 30 minutes of milling. After a total milling time of 40 hours, the ball mill was opened to obtain a gray powder.

[0073] d. Wash the powder once with ethanol by centrifugation to remove most of the caproic acid; this step d generally takes a few minutes to complete;

[0074] e. Continue to add the powder to the quartz flask in the solution of hydrogen peroxide and dilute nitric acid. The amount of solution used is: according to the mass of the powder before washing with ethanol, 30g of 2g of 65wt.% nitric acid and 28g of hydrogen peroxide containing 30wt.% hydrogen peroxide are added per gram of powder. Then, the quartz flask is placed in a 120-degree oil bath and refluxed for 15 minutes to remove tungsten carbide debris and residual organic acid; the whole process of step e takes about 30-40 minutes;

[0075] f. After the powder is separated from the solid and liquid and cooled, it is centrifugally washed twice with deionized water and then once with ethanol. This washing step takes no more than 40 minutes. The powder is then placed in a vacuum drying oven at 70 degrees for 12 hours to obtain the target powder.

[0076] Figure 7 This is the XRD spectrum of the α-alumina powder obtained in Example 3, which shows a pure α-alumina phase. The grain size is estimated by using the Scherrer formula on the XRD spectrum, and the obtained size is about 11.7 nm. Figure 8 This is a transmission electron microscope image of the α-alumina powder obtained in Example 3. It can be seen that the average particle size of the sample is about 8.5 nanometers, the particle size distribution is narrow, and the powder has good dispersibility. Fig. 9The nitrogen adsorption-desorption curve of the α-alumina powder obtained in Example 3 is a composite H3 type published by the International Union of Pure and Applied Chemistry, indicating that the obtained powder is a soft agglomerated powder, which once again proves that the powder has good dispersibility. The specific surface area of ​​α-alumina is calculated by the formula through the adsorption-desorption curve to be 137 m 2 / g. The sample purity was measured by ICP-OES and was about 99.5wt.%.

[0077] Example 4

[0078] This example uses a specific surface area of ​​170m 2 / g of γ-alumina was used as raw material, and octanoic acid CH3(CH2)6COOH was added as a grinding aid to prepare a material with a specific surface area of ​​139m 2 / g of α-alumina nanopowder. The specific steps are:

[0079] a. Place about 750 g of tungsten carbide grinding balls (i.e., the grinding medium is tungsten carbide) with a ball diameter of 1 cm in a 250 ml tungsten carbide ball mill;

[0080] b. Alumina and octanoic acid were added in an amount of 0.3mmol octanoic acid per gram of alumina to make the total weight of the material about 25 grams;

[0081] c. The ball mill was placed on a planetary ball mill (produced by Nanjing University, model QM-3SP2, with a rotation speed to revolution speed ratio of -2:1) and the revolution speed was set to 290 revolutions per minute. The ball mill was paused for 10 minutes every 30 minutes of milling. After a total milling time of 40 hours, the ball mill was opened to obtain a gray powder.

[0082] d. Wash the powder once with ethanol by centrifugation to remove most of the octanoic acid; this step d generally takes a few minutes to complete;

[0083] e. Continue to add the powder to the quartz flask in the solution of hydrogen peroxide and dilute nitric acid. The amount of solution used is: based on the mass of the powder before washing with ethanol, add 30g of nitric acid containing 2g of 65wt.% nitric acid and 28g of hydrogen peroxide containing 30wt.% hydrogen peroxide per gram of powder. Then put the quartz flask into a 120-degree oil bath and reflux and boil for 15 minutes to remove tungsten carbide debris impurities and residual organic acid. The whole process of step e takes about 30-40 minutes;

[0084] f. After the powder is separated from the solid and liquid and cooled, it is centrifugally washed twice with deionized water and then once with ethanol. This washing step takes no more than 40 minutes. The powder is then placed in a vacuum drying oven at 70 degrees for 12 hours to obtain the target powder.

[0085] Fig.10This is the XRD spectrum of the α-alumina powder obtained in Example 4, showing pure α-alumina phase. The grain size was estimated from the XRD spectrum using the Scherrer formula, and the obtained size was about 12.7 nm. Fig.11 This is a transmission electron microscope image of the α-alumina powder obtained in Example 4. It can be seen that the average particle size of the sample is about 8.8 nanometers, the particle size distribution is narrow, and the powder has good dispersibility. Fig.12 The nitrogen adsorption-desorption curve of the α-alumina powder obtained in Example 4 is a composite H3 type published by the International Union of Pure and Applied Chemistry, indicating that the obtained powder is a soft agglomerated powder, which once again proves that the powder has good dispersibility. The specific surface area of ​​α-alumina is calculated by the adsorption-desorption curve using the formula: 139 m 2 / g. The sample purity was measured by ICP-OES and was about 99.5wt.%

[0086] Example 5

[0087] This example uses a specific surface area of ​​170m 2 / g of γ-alumina was used as raw material, and decanoic acid CH3(CH2)8COOH was added as a grinding aid to prepare a grinding aid with a specific surface area of ​​150m 2 / g of α-alumina nanopowder. The specific steps are:

[0088] a. Place about 750 g of tungsten carbide grinding balls (i.e., the grinding medium is tungsten carbide) with a ball diameter of 1 cm in a 250 ml tungsten carbide ball mill;

[0089] b. Alumina and decanoic acid were added in an amount of 0.3 mmol decanoic acid per gram of alumina raw material so that the total weight of the material was about 25 g;

[0090] c. The ball mill was placed on a planetary ball mill (produced by Nanjing University, model QM-3SP2, with a rotation speed to revolution speed ratio of -2:1) and the revolution speed was set to 290 revolutions per minute. The ball mill was paused for 10 minutes every 30 minutes of milling. After a total milling time of 40 hours, the ball mill was opened to obtain a gray powder.

[0091] d. Wash the powder once by centrifugation with ethanol to remove most of the lauric acid; this step d generally takes a few minutes to complete;

[0092] e. Continue to add the powder to the quartz flask in the solution of hydrogen peroxide and dilute nitric acid. The amount of solution used is: based on the mass of the powder before washing with ethanol, 30g of 2g of 65wt.% nitric acid and 28g of hydrogen peroxide containing 30wt.% hydrogen peroxide are added per gram of powder. Then, the quartz flask is placed in a 120-degree oil bath and refluxed for 15 minutes to remove WC and residual organic acid; the whole process of step e takes about 30-40 minutes;

[0093] f. After the powder is separated from the solid and liquid and cooled, it is centrifugally washed twice with deionized water and then once with ethanol. This washing step takes no more than 40 minutes. The powder is then placed in a vacuum drying oven at 70 degrees for 12 hours to obtain the target powder.

[0094] Fig.13 This is the XRD spectrum of the α-alumina powder obtained in Example 5, which shows a pure α-alumina phase. The grain size is estimated by using the Scherrer formula on the XRD spectrum, and the obtained grain size is about 12.8 nm. Fig.14 This is a transmission electron microscope image of the α-alumina powder obtained in Example 5. The average particle size of the particles obtained from the transmission electron microscope image is about 9.4 nanometers, the particle size distribution is narrow, and the powder has good dispersibility. Fig.15 The nitrogen adsorption-desorption curve of the α-alumina powder obtained in Example 5 is a composite H3 type published by the International Union of Pure and Applied Chemistry, indicating that the obtained powder is a soft agglomerated powder, which once again proves that the powder has good dispersibility. The specific surface area of ​​α-alumina is calculated by the formula through the adsorption-desorption curve to be 150m 2 / g. The sample purity was measured by ICP-OES and was about 99.5wt.%.

[0095] Example 6

[0096] This example uses a specific surface area of ​​170m 2 / g of γ-alumina as raw material, by adding lauric acid CH3(CH2) 10 COOH was used as a grinding aid to prepare a specific surface area of ​​151m 2 / g of α-alumina nanopowder. The specific steps are:

[0097] a. Place about 750 g of tungsten carbide grinding balls (i.e., the grinding medium is tungsten carbide) with a ball diameter of 1 cm in a 250 ml tungsten carbide ball mill;

[0098] b. Alumina and lauric acid were added in an amount of 0.3mmol lauric acid per gram of alumina raw material to make the total weight of the material be about 25 grams;

[0099] c. The ball mill was placed on a planetary ball mill (produced by Nanjing University, model QM-3SP2, with a rotation speed to revolution speed ratio of -2:1) and the revolution speed was set to 290 revolutions per minute. The ball mill was paused for 10 minutes every 30 minutes of milling. After a total milling time of 45 hours, the ball mill was opened to obtain a gray powder.

[0100] d. Wash the powder once by centrifugation with ethanol to remove most of the lauric acid; this step d generally takes a few minutes to complete;

[0101] e. Continue to add the powder to the quartz flask in the solution of hydrogen peroxide and dilute nitric acid. The amount of solution used is: according to the mass of the powder before washing with ethanol, 30g of 2g of 65wt.% nitric acid and 28g of hydrogen peroxide containing 30wt.% hydrogen peroxide are added per gram of powder. Then, the quartz flask is placed in a 120-degree oil bath and refluxed for 15 minutes to remove tungsten carbide debris 1 and residual organic acid; the whole process of step e takes about 30-40 minutes;

[0102] f. After the powder is separated from the solid and liquid and cooled, it is centrifugally washed twice with deionized water and then once with ethanol. This washing step takes no more than 40 minutes. The powder is then placed in a vacuum drying oven at 70 degrees for 12 hours to obtain the target powder.

[0103] Fig.16 This is the XRD spectrum of the α-alumina powder obtained in Example 6, which shows a pure α-alumina phase. The grain size is estimated by using the Scherrer formula on the XRD spectrum, and the obtained grain size is about 12.4 nm. Fig.17 This is a transmission electron microscope image of the α-alumina powder obtained in Example 6. The average particle size of the particles obtained from the transmission electron microscope image is about 9.7 nanometers, the particle size distribution is narrow, and the powder has good dispersibility. Fig.18 The nitrogen adsorption-desorption curve of the α-alumina powder obtained in Example 6 is a composite H3 type published by the International Union of Pure and Applied Chemistry, indicating that the obtained powder is a soft agglomerated powder, which once again proves that the powder has good dispersibility. The specific surface area of ​​α-alumina is calculated by the adsorption-desorption curve using the formula: 151m 2 / g. The sample purity was measured by ICP-OES and was about 99.5wt.%.

[0104] Example 7

[0105] This example uses a specific surface area of ​​170m 2 / g of γ-alumina as raw material, by adding myristic acid CH3(CH2) 12 COOH was used as a grinding aid to prepare a specific surface area of ​​132 m 2 / g of α-alumina nanopowder. The specific steps are:

[0106] a. Place about 750 g of tungsten carbide grinding balls (i.e., the grinding medium is tungsten carbide) with a ball diameter of 1 cm in a 250 ml tungsten carbide ball mill;

[0107] b. Alumina and myristic acid were added in an amount of 0.3mmol per gram of alumina raw material to make the total weight of the material about 25 grams;

[0108] c. The ball mill was placed on a planetary ball mill (produced by Nanjing University, model QM-3SP2, with a rotation speed to revolution speed ratio of -2:1) and the revolution speed was set to 290 revolutions per minute. The ball mill was paused for 10 minutes every 30 minutes of milling. After a total milling time of 45 hours, the ball mill was opened to obtain a gray powder.

[0109] d. Wash the powder once with ethanol by centrifugation to remove most of the myristic acid; this step d generally takes a few minutes to complete;

[0110] e. Continue to add the powder to the quartz flask in the solution of hydrogen peroxide and dilute nitric acid. The amount of solution used is: according to the mass of the powder before washing with ethanol, 30g of 2g of 65wt.% nitric acid and 28g of hydrogen peroxide containing 30wt.% hydrogen peroxide are added per gram of powder. Then, the quartz flask is placed in a 120-degree oil bath and refluxed for 15 minutes to remove tungsten carbide debris and residual organic acid; the whole process of step e takes about 30-40 minutes;

[0111] f. After the powder is separated from the solid and liquid and cooled, it is centrifugally washed twice with deionized water and then once with ethanol. This washing step takes no more than 40 minutes. The powder is then placed in a vacuum drying oven at 70 degrees for 12 hours to obtain the target powder.

[0112] Fig.19 This is the XRD spectrum of the α-alumina powder obtained in Example 7, which shows a pure α-alumina phase. The grain size is estimated by using the Scherrer formula on the XRD spectrum, and the obtained grain size is about 12.9 nm. Fig. 20 This is a transmission electron microscope image of the α-alumina powder obtained in Example 7. The average particle size of the particles obtained from the transmission electron microscope image is about 10.1 nanometers, the particle size distribution is narrow, and the powder has good dispersibility. Fig.21 The nitrogen adsorption-desorption curve of the α-alumina powder obtained in Example 7 is a composite H3 type published by the International Union of Pure and Applied Chemistry, indicating that the obtained powder is a soft agglomerated powder, which once again proves that the powder has good dispersibility. The specific surface area of ​​α-alumina is calculated by the formula through the adsorption-desorption curve to be 132 m 2 / g. The sample purity was measured by ICP-OES and was about 99.5wt.%.

[0113] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing α-alumina nanopowder with large specific surface area, wherein the nanopowder refers to a powder with an average particle size of less than 15 nanometers, and the large specific surface area refers to a BET surface area greater than 100 m 2 / g, characterized in that The following steps are involved: A) grinding a mixture of alumina raw material and an organic acid grinding aid with a grinding medium, wherein the grinding aid is an organic acid.

2. The preparation method according to claim 1, characterized in that: The alumina raw material has no limitation on crystal form and initial particle size.

3. The preparation method according to claim 1, characterized in that: The alumina is selected from thermodynamically metastable transition phase aluminas such as amorphous alumina, γ alumina, δ alumina, η alumina, θ alumina, λ alumina, κ alumina, ρ alumina, χ alumina, and α alumina, or a mixture of at least two of them; the organic acid is selected from carboxylic acid, organic sulfonic acid, organic sulfinic acid, or thiocarboxylic acid.

4. The preparation method according to claim 1, characterized in that: The grinding is selected from planetary ball milling, vibrating ball milling, stirring ball milling or bead milling.

5. The preparation method according to claim 1, characterized in that: The ratio of the organic acid grinding aid to the alumina raw material is 0.1-1 mmol / g.

6. The preparation method according to claim 1, characterized in that: The grinding media are stainless steel balls, tungsten steel balls, corundum balls, zirconium dioxide balls or tungsten carbide balls, the ball-to-material mass ratio is 10:1 to 60:1, the ball mill speed is 200-500rpm, the grinding temperature is room temperature to 200°C, and the grinding time is 10 to 70 hours.

7. The preparation method according to claim 1, characterized in that: After step A), the following steps are also included: B) preliminarily removing the organic acid grinding aid contained in the ground powder by solvent washing; C) adding the ground powder to a mixed solution of an inorganic acid and an oxidant to remove grinding medium debris and residual organic acid grinding aids; D) washing the powder after removing the grinding medium debris and the organic acid grinding aid with an inert solvent, and then vacuum drying to obtain a pure large specific surface area α-alumina nanopowder; Step B can be omitted.

8. The preparation method according to claim 7, characterized in that: The inorganic acid is selected from nitric acid, sulfuric acid, and hydrochloric acid, and the oxidant is selected from hydrogen peroxide, persulfuric acid, perchloric acid, or sodium hypochlorite.

Citation Information

Patent Citations

  • Preparation method of completely-dispersed aluminum oxide nanoparticles

    CN104495891A

  • Preparation method of completely-dispersible alpha alumina nanoparticles

    CN106044809A